Seasonal Variations of Algae in Relation to the Water Quality at Kingfisher Lake, Central Nepal - Dhakal, Sajita; Ghimire, Narayan Prasad; Rai, Shiva Kumar; Dhakal, Sandesh (Journal of Plant Resources, 2022)
Algae can be found in the sea, freshwater and wastewater all around the world. Although the majority is microscopic, some are large. In this study, a total of 44 samples, were collected in two seasons (pre-monsoon and post-monsoon) in the years 2021-2022 from Kingfisher Lake, located in the Bharatpur, Chitwan District. A total of 51 algal species belonging to six classes were recorded. Information on the distribution of algal flora of Kingfisher Lake was collected and the data revealed that the dominant members belong to the classes Bacillariophyceae and Zygnematophyceae, each having 15 species; followed by Chlorophyceae, Cyanophyceae and Euglenophyceae. Similarly, the physico-chemical parameters of water were measured by a digital portable multiparameter (HI98194) in the field. Water temperature was low during post-monsoon season. Electrical conductivity, Total Dissolved Solids (TDS), Oxidation Reduction Potential and Dissolved Oxygen were high in post-monsoon season while the pH of the lake water was alkaline and low pH in post-monsoon season. The number of algal species was found higher in pre-monsoon season than in post-monsoon season. The study showed that the lake is rich in algal species. Presence of the species like Closterium sp. and Oscillatoria sp. indicate that the lake is eutrophicated and polluted. Thus, further investigations were needed.